Development of an international core domain set for medium, large and giant congenital melanocytic naevi as a first step towards a core outcome set for clinical practice and research. (1st March 2021) - Oei, W.; Fledderus, A.C.; Spuls, P.I; Eggen, C.A.M.; Kottner, J.; van der Horst, C.M.A.M.; Wolkerstorfer, A.; van Kessel, M.S.; Krengel, S.; Etchevers, H.C.; Korfage, I.J.; Pasmans, S.G.M.
Summary: Background: Medium, large and giant congenital melanocytic naevi (CMN) can impose a psychosocial burden on patients and families, and are associated with increased risk of developing melanoma or neurological symptoms. Lack of consensus on what outcomes to measure makes it difficult to advise patients and families about treatment and to set up best practice for CMN. Objectives: Fostering consensus among patient representatives and professionals, we aim to develop a core outcome set, defined as the minimum set of outcomes to measure and report in care and all clinical trials of a specific health condition. We focused on the 'what to measure' aspect, the so‐called core domain set (CDS), following the COMET and CS‐COUSIN guidelines. Methods: We conducted a systematic review to identify outcomes reported in the literature. Focus groups with patient representatives identified patient‐reported outcomes. All these outcomes were classified into domains. Through e‐Delphi surveys, 144 stakeholders from 27 countries iteratively rated the importance of domains and outcomes. An online consensus meeting attended by seven patient representatives and seven professionals finalized the CDS. Results: We reached consensus on six domains, four of which were applied to both care and research: 'quality of life', 'neoplasms', 'nervous system' and 'anatomy of skin'. 'Adverse events' was specific to care and 'pathology' to research. Conclusions: We have developed a CDS for medium‐to‐giant CMN. Its application in reporting care and research of CMN will facilitate treatment comparisons. The next step will be to reach consensus on the specific outcomes for each of the domains and what instruments should be used to measure these domains and outcomes. Abstract : What is already known about this topic? Medium, large and giant congenital melanocytic naevi (CMN) are associated with psychosocial burden for patients and their families because of their unusual appearance and increased risk of melanoma and/or neurocutaneous melanocytosis. Outcome reporting of treatment options for CMN is heterogeneous. Current lack of consensus in outcome reporting hinders the development of evidence‐based treatment guidelines for CMN. Development of a core outcome set (COS) may enhance standardized reporting. What does this study add? We focus on the core domain set, the 'what to measure', for the COS. By following the guidelines of COMET and CS‐COUSIN, we reached consensus on six domains. Four of the domains were applied to both care and research: 'quality of life', 'neoplasms', 'nervous system' and 'anatomy of skin'. 'Adverse events' was specific to care and 'pathology' to research. What are the clinical implications of this work? Uptake of the core domain set in future clinical care of, and research about, medium‐to‐giant CMN should facilitate comparisons across different treatment choices for both patients and professionals. Linked Comment: M.V. Heppt et al. Br J Dermatol 2021; 185 :247–248 . Plain language summary available online